Avaliação do efeito da temperatura na farmacocinética de florfenicol e na oxidação lipídica de filés de tilápias (Oreochromisniloticus) - Rubim, Fernando Marcos (2021)
As fish is one of the most consumed animal protein sources in the world, the concern with sanitary measures for the flocks and with the quality of the products produced is becoming increasingly latent. The search for more assertive therapeutic actions is an important factor for the sanitary viability of production, for public health and a potential influence on the quality of the meat produced. This study aimed to evaluate the influence of temperature on the pharmacokinetic profile of animals undergoing treatment, aiming at drug optimization, therapeutic efficiency and food safety. A total of 204 animals (Oreochromis niloticus) were subjected to different temperatures, being divided into four groups of 14ºC, 21ºC, 28ºC and 32ºC during treatment with florfenicol at 10mg/kg for 10 consecutive days orally, and in 500ppm and 200ppm in concertations in soaking bath for 5 days. Subsequently, the Monolix 2020 program from Lixoft® was used for pharmacometric analysis and determination of pharmacokinetic parameters, observing the variation of these parameters in relation to the temperature at which the animals were raised. Oxidation conditions of the files were also evaluated, to establish a probable correlation between drug use and changes in the shelf life of the product, where a relationship between the temperature of creation and the oxidation of the fillets was not observed.